Digital vs screen-film mammography in population-based breast cancer screening: performance indicators and tumour characteristics of screen-detected and interval cancers - de Munck, Linda (Br J Cancer, 2016)
BACKGROUND: Full-field digital mammography (FFDM) has replaced screen-film mammography (SFM) in most breast cancer screening programs due to technological advantages such as possibilities to adjust contrast, better image quality and transfer capabilities. This study describes the performance indicators during the transition from SFM to FFDM and the characteristics of screen-detected and interval cancers. METHODS: Data of the Dutch breast cancer screening program, region North from 2004 to 2010 were linked to The Netherlands Cancer Registry (N=902 868). Performance indicators and tumour characteristics of screen-detected and interval cancers were compared between FFDM and SFM. RESULTS: After initial screens, recall rates were 2.1% (SFM) and 3.0% (FFDM; P<0.001). The positive predictive values (PPV) were 25.6% (SFM) and 19.9% (FFDM; P=0.002). Detection rates were similar, as were all performance indicators after subsequent screens. Similar percentages of low-grade ductal carcinoma in situ (DCIS) were found for SFM and FFDM. Invasive cancers diagnosed after subsequent screens with FFDM were more often of high-grade (P=0.024) and ductal type (P=0.030). The incidence rates of interval cancers were similar for SFM and FFDM after initial (2.69/1000 vs 2.51/1000; P=0.787) and subsequent screens (2.30 vs 2.41; P=0.652), with similar tumour characteristics. CONCLUSIONS: FFDM resulted in similar rates of screen-detected and interval cancers, indicating that FFDM performs as well as SFM in a breast cancer screening program. No signs of an increase in low-grade DCIS (which might connote possible overdiagnosis) were seen. Nonetheless, after initial screening, which accounts for 12% of all screens, FFDM resulted in higher recall rate and lower PPV that requires attention.